Impacto del envejecimiento en la susceptibilidad al daño por humedad en mezclas asfálticas (2020)
Moisture damage and aging of asphalt mixes are associated with the durability of the material. Few studies have assessed the impact that the coupling of these damage processes has on the asphalt mixture. The objective of this research is to determine the impact of three aging states of an asphalt mixture (HMA-25) on the moisture damage of the material, measured under two different moisture conditioning states. Also, the study evaluated the coupled effects of these two phenomena on the dynamic modulus of the asphalt mixture. The mixture was design using the SUPERPAVE methodology, obtaining an optimum asphalt percentage of 4.9% by total weight of the mixture. The mixture was initially aged in loss state under three conditions: 1) short-term, 2) long-term (4 days in the oven at 95ðC), and 3) long-term (10 days in the oven at 95ðC). Afterwards the mixtures were tested in two states: 1) after compaction (dry state) and 2) after compaction and being subjected to a moisture conditioning process (i.e., ¿wet? state). For short-term aging, the indirect tensile strength in wet state fell 20% with respect to the dry condition, for long-term aging 1 it fell 2%, and for long-term aging 2 it fell 21%. With respect to the dynamic modulus at 20 C, for the short-term aging state, the modulus of the wet group fell 11% on average with respect to the dry group, while for long-term aging 2 it fell 56%. In the case of long-term aging 1, the reduction could not be quantified due to the variability of the data. The results of the indirect traction tests do not allow determining a clear increase in the susceptibility to moisture damage of the mixture with aging. However, the dynamic modulus results show a significant reduction in the mix stiffness in wet condition with respect to the dry condition for long term aging 2, which indicates that the susceptibility to moisture damage changes depending on the pavement service time.